SAT0132 Comorbidities affect the retention rate but not the clinical response in a cohort of rheumatoid arthritis patients treated with tumor necrosis factor inhibitors. (12th June 2018) - Favalli, E. G.; Biggioggero, M.; Becciolini, A.; Crotti, C.; Sinigaglia, L.
Abstract : Background: Rheumatoid arthritis(RA) is frequently complicated by other comorbid diseases that may drivetherapeutic strategy or interfere with achieving clinical response. Objectives: To retrospectively evaluate the impact of comorbidities on treatment choice, 12-month clinical response, and 24-month retention rate in a cohort of RA patients treated with a first-line subcutaneous tumour necrosis factor alpha inhibitor (TNFi). Methods: Study population was extracted from a local registry which included all RA patients receiving adalimumab (ADA) or etanercept (ETN) as first-line biologic drug between January 2001 and December 2013. The prevalence of common RA comorbidities was computed and the study population was stratified according to Rheumatic Disease Comorbidity Index ([RDCI 1 ] RDCI=0 vs RCDI≥1) for evaluating the role of comorbidities on the choice between ETN and ADA; the prescription of concomitant methotrexate (MTX); and the impact of comorbidities on 1-yearDisease Activity Score 28 (DAS28-ESR) remission and EULAR good-moderateresponse rates. The 24-month retention rate was computed by the Kaplan-Meiermethod and a Cox proportional hazard model was developed to examine the role ofRDCI and other baseline factors as predictors of TNFi persistence. Results: 310 RA patients (153ADA and 157 ETN) were included (female 82.1%, mean±standard deviation (SD) age 53.6±13.1 years, mean disease duration 11.6±9.2 years, mean baseline DAS 285.28±1.21, RF positivity 76.4%, mean HAQ 1.39±0.56). 41.2% of patients had atleast one comorbidity (overall mean RDCI 0.73) and the prevalence of conditions is reported in table 1. The proportion of patients with RCDI≥1 was similar in the subgroup receiving or not concomitant MTX (55.1% versus 44.8%, respectively; p=0.57) and similar (p=0.22) in patients treated with ADA (44.8%) or ETN (37.8%). No individual comorbidity was associated with the prescription of MTX or the choice between the two TNFis. No difference was found in therates of both EULAR good-moderate response (61.3% vs 53.7%, p=0.175) and DAS28-ESR remission (31.4% vs 27.2, p=0.463) according to baseline RDCI score. On the other hand, elevated RDCI is a predictor of biologic drug discontinuation (Hazard Ratio [HR] 1.17, confidence interval [95% CI] 1.00-1.37;p=0.04), where as treatment with ETN (HR 0.50, 95% CI 0.35-0.71; p<0.001) and concomitant MTX (HR 0.57, 95% CI 0.40-0.81; p=0.002) were both associated with a lower risk of TNFi withdrawal. Conclusions: in our real-life experience, the baseline presence of comorbidity seemed to not influence the prescription of concomitant MTX and to not drive the choice between ADA and ETN. Comorbidities did not affect 1-year clinical response, but were associated with a higher risk of TNFi discontinuation over a 2-year follow-up period. The use of ETN and concomitant treatment with MTX were both strong predictors of drug persistence. Reference: 1. England BR, Sayles H, Mikuls TR, et al. Validation of the rheumatic diseasecomorbidity index. Arthritis Care Res 2015;67(6):865-72. Disclosure of Interest: None declared